Etiology and Antimicrobial Susceptibility Patterns of Urinary Tract Infection at Dhaka Shishu (children) Hospital (Northern International Medical College Journal, 2017)
Background : Urinary tract infection (UTI) is a common bacterial disease in infant and childhood period that can present as symptomatic or asymptomatic way.Antibiotic resistance of urinary tract pathogens has been known to increase worldwide, especially to commonly used antimicrobials. Knowledge of pathogens causing UTI and their antimicrobial resistance patterns in a specific geographical location may help clinicians in choosing the appropriate antimicrobial agent.Objective : The objective of this study was to find out the pathogens in pediatric UTI and their antimicrobial susceptibility pattern.Methods : A cross sectional study was done at Dhaka shishu Hospital during the period of Feb 2016 to Aug 2016. A total of 147 culture positive UTI patient were taken for analysis. Colony counts of these samples, were identified, and the profile of antibiotic susceptibility was identified. Here, samples with a colony count of 105 CFU/mL bacteria were considered positive.Twelve (12) antimicrobial agent were used for antimicrobial susceptibility testing.Result : Among 147 culture positive UTI patients Escherichia coli (E-coli) was found as the most prevalent 103(70%) followed by Klebsiella spp. 13.6%, Enterobacterspp 3.40%, Pseudomonas 5.44%, Staphylococcus Aureus 3.40%, Enterococcus 1.36% and Proteus 2.72%. The most effective drugs found against urinary isolates was Imepenum (97.27%), followed by Colistin (94.55%), Meropenum (93.87%) and Amikacin (91.83%). E.coli was moderately sensitive to Ceftraxone, Ceftazidime, Nitrofurantoin and Ciprofloxacin.Conclusion : In this study, Imipenum, Meropenum, Amikacin and Colistin shown to be the most sensitive antibiotics for the UTI pathogen. Antimicrobial drug resistance is increasing among urinary pathogens. Therefore, empirical antibiotic selection should be based on knowledge of the local prevalence of bacterial organism and their antibiotic susceptibility in a specific area rather than on universal or even national guidelines.Northern International Medical College Journal Vol.8(2) January 2017: 220-223